Protectionism and national migration policy in South Africa - Boynton, Elspeth Whitney (Department of Political Studies, 2016)
In the past two decades, South Africa has become the "new migration hub" in Africa. The country has witnessed the dramatic rise of people flowing into its borders post-apartheid from the continent and beyond. However, in response to the large influx of migrants (legal and illegal), South Africa has adopted protectionist and nationalistic migration policies, emphasizing border control, rather than migration facilitation or migrant protection. Despite South Africa's post-apartheid commitments to human rights, democracy, and Pan-Africanism, the restrictive nature of these laws has led to the mistreatment and neglect of refugee and asylum seekers, the unlawful detention and deportation of legal in-migrants, and the failure to address societal xenophobia. These policies have also contributed to a severe skills shortage in South Africa, impeding the growth of the South African economy, while also thwarting SADC's ability to govern migration cooperatively in the region. In light of the most recent migration reforms implemented in 2014, instigating more protectionism, this thesis examines and seeks to explain why South Africa has adopted and continues to maintain these policies post-apartheid despite their negative implications and lack of congruence with South Africa's new national identity. The international relations theories of constructivism and neoclassical realism (NCR) are used to understand and explain South Africa's decision to maintain a protectionist migration agenda. Ultimately, the thesis argues that South Africa's reasons for adopting a protectionist migration agenda are numerous and exist at all levels of analysis. These reasons include (1) South Africa's formation of an exclusionary national identity post-apartheid, (2) the persistence of mass legal and illegal in-migration to the country, (3) the institutionalized perception of migration as a threat to national and social security by South African policy-makers/media/community leaders, and (4) the failure of the state to provide adequate social service delivery, impacting the implementation of more liberal policies in the new millennium.